Improving Learning Outcome on Pillars of Faith through Index Card Match Method in Class 1 - Farid, Iip Miptah; Ginanjar, Ani Yanti (Al-Aulad: Journal of Islamic Primary Education, 2023)
This study aims to determine: 1) the implementation of the Index Card Match Method. 2) the improvement of students' learning achievement in the material of the Pillars of Islam through the implementation of the Index Card Match Method in Class I of SDN Rancalongong 01. This research is a classroom action research using a qualitative approach, although simple quantitative analysis strategies are also used to describe the percentage increase in Islamic Religious Education (PAI) learning outcomes in the Pillars of Faith material for Class I students of SDN Rancalongong 01. Data collection methods used in this study include: 1) observation. 2) Documentation. 3) Tests. 4) Interviews. Then, the results of this research are reviewed from planning, implementation, observation, and reflection to reaching conclusions. The conclusion of this research is that: 1) The implementation of the Index Card Match Method in Class I of SDN Rancalongong 01. The implementation of PAI learning in Class I of SDN Rancalongong 01 conducted by teachers is less satisfactory in reality. The implementation of the Index Card Match Method in this subject can be accepted with a positive response from students, which consistently increases significantly. Step-by-step learning activities towards student learning activities can improve PAI learning outcomes in the Pillars of Faith material to keep students actively engaged in learning.